A newly proposed method for Weibull parameters estimation and assessment of wind potential in Southern Punjab - Muhammad Sumair; Tauseef Aized; Syed Asad Raza Gardezi; Syed Ubaid ur Rehman; Syed Muhammad Sohail Rehman (Energy Reports, 2020)
Accuracy of wind potential estimation using two-parameter Weibull distribution relies on the accuracy with which Weibull distribution models the wind data. Therefore, there is always a thirst for developing better methods for the estimation of Weibull parameters. Current work focusses on the investigation of a newly proposed method called Modified Method of Moment (MMOM) and comparing it with two other methods i.e. Energy Pattern Factor Method (EPFM) and Method of Moment (MOM) to assess wind potential in South Punjab. Five years (2014-2018) hourly wind data measured at 50 m height and collected from Pakistan Meteorological Department (PMD) was utilized. Performance of EPFM, MOM and MMOM was evaluated using coefficient of determination, root mean square error and power error. Monthly, seasonal and annual variations in wind speed, wind power density (WPD) and wind energy density (WED) were analyzed and annual energy production using six turbine models was also estimated. The analysis showed that MMOM is the best method followed by MOM and EPFM respectively. Furthermore, the highest wind potential is observed in summer while lowest in winter in whole region. Polar diagrams showed that the optimum wind direction in the area is southwest.
Keywords: 330; Capacity factor; Energy pattern factor method; Energy production from wind turbines; Method of moment; Modified method of moment; Wind potential assessment in South Punjab